Care course in children with Specific Language and Learning Disorders - Delteil, Florence (Bulletin de l'Académie nationale de médecine, 2015)
Specific language and learning disorders concern about 5 %l of the population and explain a significant proportion of educational difficulties and schoolfailure in France. If they are not recognized in time, they can lead to school exclusion if not illiteracy. Reference Centers for specific language and learning disorders were created in the 2000's and improved consis- tently diagnosis and management of such disorders but there remain many difficulties: appointment's delay in these centers, professional training, limited care access in some areas and financial support for specific checkups and cares insufficiently refunded by the Health services, excluding low-income people. Another problem is the lack of care for teenagers and adults after the period covered by Reference Centers. This subject should be a national public health priority to avoid lifelong consequences in social and professional integration. Measures are evoked to improve this situation.